Modeling the Great Lakes Basin based on dynamic network flows - Gao, Huiyang (Transactions on Environment, Energy and Earth Sciences, 2024)
The Great Lakes are the largest freshwater lakes in the world and involve various stakeholders. the paper develop a Basin model of the Great Lakes based on dynamic network flow and propose an optimization algorithm for dam control to obtain the best water level.First, We regard lakes and rivers in the Great Lakes as edges and nodes of a dynamic network flow to build a Dynamic Hydrological Network Flow Model where the capacity of edges relate to lakes’maximum water levels and flow is transmitted through the rivers. To explore the interaction between lakes and rivers in the basin, the paper first model lakes by establishing a water balance equation that analyzes the change in water level and fitting results to confirm the correctness of our model. Then the paper use collected data to reveal that the flow depends on the water level of the upstream and downstream Lakes. Finally, analyze the mutual relation between lakes and rivers in the St. Lawrence Basin.